VALIDATION OF PSYCHOLOGICAL WELL-BEING MEASUREMENT ITEMSUSING CONTENT VALIDITY RATIO TECHNIQUE - Muktar, Masyitahfatimah binti; Matore, Mohd Effendi Ewan bin Mohd (The journal of contemporary issues in business and government, 2021)
The literature has emerged that offers contradictory findings about psychological well-being but the information among education officer was limited. Until recently, there has been no reliable evidence of psychological well-being measurement using experts consensusin Malaysia. This study aims to obtainthe validity ofpsychological well-being measurement items amongSchool Improvement Specialist Coaches Plus (SISC+) and School Improvement Partner Plus (SIPartners+) officers through expert consensuswith the Content Validity Ratio or CVR methodby Lawshe (1975).This quantitative method uses a survey design through questionnaireswhilethe sampling technique includespurposive sampling,namely judgement sampling that comprisesthirteen experts inthe fields of counseling, psychology, psychometric, and language. Content validity involves fifty-four items with six dimensions adapted from Ryff’s Scales of Psychological Well-Being(1989).Overall findings recorded N=13, minimum value=0.54, and CVR=9 itemsrefined.Allpsychological well-being itemsthat have undertakencontent validitywere suggested to proposedin order to conduct a pilot studyon SISC+ and SIPartners+ officers usingthe Rasch Measurement Model.